Who Are Better Informed Before Analystsâ Forecast Changes? - Park, Tae-Jun; Yi, Sujin; Song, Kyojik Ã¢Â€ÂœRoyÃ¢Â€Â (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
Using Korean data, we investigate information asymmetry among investors before analysts change their stock recommendations. By comparing trading activities between individuals, institutions, and foreign investors, we find that there is information asymmetry before analysts change their recommendations. Institutional investors buy/sell the stock before recommendation upgrades/downgrades, but individuals and foreign investors do not anticipate the upcoming news. We also document that the trade imbalance of institutional investors are associated with stock returns upon the announcements of recommendation changes. This result indicates that institutions take advantage of their superior information around the recommendation changes.Â Â Â Â Â Â